(untitled) (TAMADDUN NURI JURNALI, 2025)
Today, the development of flexibility in preschool children is one of the most pressing issues. Physical exercises currently used in practice often have only an indirect impact on this physical quality and do not fully ensure the adequate development of flexibility. As a result, there is a lack of effective and optimal approaches aimed at the comprehensive development of flexibility in children. This leads to a new challenge for educators and specialists: the need to find effective methods and tools that allow children to master physical movements quickly and improve their overall physical readiness in a short period.